A phase IIa randomised clinical study of GNbAC1, a humanised monoclonal antibody against the envelope protein of multiple sclerosis-associated endogenous retrovirus in multiple sclerosis patients. (June 2015) - Derfuss, Tobias; Curtin, François; Guebelin, Claudia; Bridel, Claire; Rasenack, Maria; Matthey, Alain; Du Pasquier, Renaud; Schluep, Myriam; Desmeules, Jules; Lang, Alois B; Perron, Hervé; Faucard, Raphael; et al.
Background: GNbAC1 is an immunoglobulin (IgG4) humanised monoclonal antibody against multiple sclerosis-associated retrovirus (MSRV)-Env, a protein of endogenous retroviral origin, expressed in multiple sclerosis (MS) lesions, which is pro-inflammatory and inhibits oligodendrocyte precursor cell differentiation. Objective: This is a randomised, double-blind placebo-controlled dose-escalation study followed by a six-month open-label phase to test GNbAC1 in MS patients. The primary objective was to assess GNbAC1 safety in MS patients, and the other objectives were pharmacokinetic and pharmacodynamic assessments. Methods: Ten MS patients were randomised into two cohorts to receive a single intravenous infusion of GNbAC1/placebo at doses of 2 or 6 mg/kg. Then all patients received five infusions of GNbAC1 at 2 or 6 mg/kg at four-week intervals in an open-label setting. Safety, brain magnetic resonance imaging (MRI), pharmacokinetics, immunogenicity, cytokines and MSRV RNA expression were studied. Results: All patients completed the study. GNbAC1 was well tolerated in all patients. GNbAC1 pharmacokinetics is dose-linear with mean elimination half-life of 27–37 d. Anti-GNbAC1 antibodies were not detected. Cytokine analysis did not indicate an adverse effect. MSRV-transcripts showed a decline after the start of treatment. Nine patients had stable brain lesions at MRI. Conclusion: The safety, pharmacokinetic profile, and pharmacodynamic responses to GNbAC1 are favourable in MS patients over a six-month treatment period.